2014
DOI: 10.1080/09654313.2014.970131
|View full text |Cite
|
Sign up to set email alerts
|

The Micro-foundations of Regional Branching—the Case of Digitization of Publishing

Abstract: Theorizing within evolutionary economic geography (EEG) on regional branching of industries has so far been depicted as evolving through routine replication among different economic actors that hold various degrees of relatedness. Methodologically related and unrelated variety has been studied quantitatively, treating relatedness between economic agents as pre-defined industrial classifications. This represents a need for a complementary qualitative and in-depth understanding of how knowledge is re-combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…4. In the case of Norwegian newspapers, Bugge and Øiestad (2015) suggest that media firms are prone to explore a dynamic interplay between specialization and diversification; however, the available information does not facilitate an easy evaluation of the profitability of such strategies. With a broader analysis, Ferrier et al (1999) found that companies presenting a greater intensity and complexity of actions, for example through diversification, have a higher probability of surviving, however, the results are highly variable across industries.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. In the case of Norwegian newspapers, Bugge and Øiestad (2015) suggest that media firms are prone to explore a dynamic interplay between specialization and diversification; however, the available information does not facilitate an easy evaluation of the profitability of such strategies. With a broader analysis, Ferrier et al (1999) found that companies presenting a greater intensity and complexity of actions, for example through diversification, have a higher probability of surviving, however, the results are highly variable across industries.…”
Section: Notesmentioning
confidence: 99%
“…2 At a more general level,Porter (1996) argues that managing new and old technologies together may lead to the degradation of the core business.3 Prior research suggests that in many industries, diversification is correlated with poorer performance(Montgomery, 1985;Montgomery and Wernerfelt, 1988;Montgomery, 1994). 4 In the case of Norwegian newspapers,Bugge and Øiestad (2014) suggest that media firms are prone to explore a dynamic interplay between specialization and diversification, however the available information does not facilitate an easy evaluation of the profitability of such…”
mentioning
confidence: 99%
“…However, the branching perspective has been contested. For example, Tanner (2014) argues that the mechanisms through which branching occurs are rather unclear, whereas Bugge and Øiestad (2014) question how different branching mechanisms result in knowledge transfer to new application domains, and how old and new knowledge sources are combined in this process. Binz, Truffer, and Coenen (2016) argue that the emphasis on territorially-specific generic resources (primarily technological knowledge) undermines the importance of translocal linkages and extralocal resource mobilization.…”
Section: Sources Of Path Dependence and Path Creationmentioning
confidence: 99%
“…Implicitly, this view rests on an assumption that firms through their recruitment decisions and local networking behaviour are able to collectively identify and exploit the potential for growth and structural change associated with the resources that are available to them locally. This view ignores that the continuous exploration of novel – not-yet-identified – combinations of knowledge, new intersections between industries and the subsequent redefinitions of related and unrelated technologies that continuously occurs, is part and parcel of innovation and technological change itself (Bugge and Øiestad, 2015; Katila and Ahuja, 2002; Katila, 2002). Moreover, in contrast to RIS, it ignores the role and importance of institutions and policy in conditioning and mediating knowledge spillovers.…”
Section: Limitations Of Eegmentioning
confidence: 99%